ALIENATION IN MOTHERHOOD AND INTELLECTUAL LIFE: A SOCIALIST FEMINIST ANALYSIS OF SWALLOW (2019) - Amelia Resti Iffadah; Istiadah; Noornajihan Jaafar (HUMANISMA : Journal of Gender Studies, 2026)
The study explores about the representation of female alienation in Swallow (2019) by Carlo Mirabella-Davis using Alison M. Jaggar’s (1983) socialist feminist framework. Previous studies on the film mainly focus on psychological trauma and bodily autonomy, while limited research analyses female alienaton from Jaggar’s feminist perspective. This study used qualitative descriptive methods with feminist film analysis. The data consisted of 11 key scenes that show power relations in the domestic and social spheres, analyzed based on Jaggar’s two concepts of alienation, Motherhood and Intellectual Agency. The data were collected by watching the film repeatedly, transcribing relevant dialogues, and identifying scenes that show forms of alienation. The data were then interpreted through narrative characterization analysis and social context analysis. The findings show that Swallow (2019) represents motherhood alienation through control over the main character’s body and pregnancy as part of family expectations and demands. Meanwhile, from the perspective of intellectual agency, female alienation is seen in the silencing of the main character’s voice and the neglect of her decisions in both personal and social settings. This study contributes to feminist film analysis by showing how gender inequality is constructed and normalized in visual representation.